Workspace analysis of a Gough-Stewart type cable marine platform subjected to harmonic water waves. (February 2018) - Horoub, Mamon M.; Hassan, Mahir; Hawwa, Muhammad A.
Abstract: A floating cable marine platform is put forward using the 3–3 Stewart-Gough parallel manipulator as an inspiring structure. The marine platform has three degrees of freedom and is composed of a cylindrical floating structure and six mooring cables anchored to the seabed. In order to provide necessary motion compensation to impinging harmonic water wave loads, necessary mooring tensions are applied to the cables to prevent them from becoming slack under the external load. The platform is analyzed in the framework of rigid-body dynamics and water wave loading is estimated by integral methods. Workspace is identified for the cable marine platform, minimum static submerged depths are calculated, and kinematic variables are investigated for various platform positions within the marine platform workspace.